AIDS, economic growth and the HIPC initiative in Honduras - José A. Cuesta (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Success of the debt-relief HIPC and poverty-reduction PRSP initiatives demands annual growth rates of 5 percent sustained for fifteen years in Honduras. However, existing evidence on the impact of AIDS on economic growth in Africa raises concern on the viability of such growth targets in Honduras, despite incidence rates in the latter trailing long behind Africa's. Hence this paper estimates the magnitude of this threat, measured as the marginal impact of projected changes in AIDS incidence over the annual growth rates of GDP for the period 2001-10. Our estimates suggest that the mature stage of the epidemic in Honduras poses an unsubstantial threat to economic growth. This is true after substantial changes on the incidence of the epidemic, its public financing, the concentration of incomes, labor productivity gaps, and foreign capital inflows have all been simulated for the relevant period. The real threat accrues from an overoptimistically projected physical capital accumulation that proves insufficient to satisfy the demands for a viable HIPC Initiative. – AIDS ; Heavily Indebted Poor Countries ; economic growth ; foreign capital flows
Keywords: I1; O4; 330; AIDS; Schuldenerlass; Wirtschaftswachstum; Honduras; Makroökonomischer Einfluss